Critical Thinking in a Learner Literary Corpus Thematic Extrapolations in Hemingway’s A Farewell to Arms. - Khachan, Victor; Bacha, Nahla Nola (International Journal of Arabic-English Studies (IJAES), 2026)
The teaching/learning of English literature to university EFL/ESL students has been essential to the development of their critical thinking skills. Using a corpus linguistics approach, the present study investigates the extent to which learners’ critical awareness is apparent through their analysis and interpretations of the characters and themes in the novel, A Farewell to Arms (1929), by Ernest Hemingway. A literary learner corpus of 206 literary argumentative essays was compiled from a '20th Century American Novel' course at an English-medium university in Lebanon. The essays were quantitatively analyzed to investigate prevalent thematic trends. This study was able to draw thematic differences between Hemingway’s novel and the learners’ literary analytic interpretations. The main findings indicated that the learners’ collocational networks strongly supported Hemingway’s stylistic ‘iceberg principle’- a critical thinking-based expectation Hemingway had for his readers. Most importantly, this lexical analysis revealed a clear ‘genre’ shift from narration in Hemingway’s A Farewell to Arms Corpus to argumentation in the Learner Literary Corpus. Overall, this study underscores the importance of literature courses in developing students’ critical thinking skills and the role corpus linguistics can play in quantifying ‘critical thinking’ measures in literature.